Implementation of Legal Protection for Child Victims of the Crime of Sexual Intercourse in terms of the Fulfillment of the Right to Restitution - Mantali, Avelia Rahmah Y (Indonesian Journal of Advocacy and Legal Services, 2022)
The fulfillment of the right of restitution against child victims of criminal acts is regulated in Article 71 letter d of Law Number 35 of 2014 concerning Child Protection. In order to make it easier for victims to get compensation without having to go through the usual civil lawsuit process, the state provides a way through merging cases of compensation claims to criminal cases regulated in Articles 98-101 of the Criminal Procedure Code. In fact, the fulfillment of the right of restitution as stated in the provisions has never been implemented. This study aims to analyze the implementation of legal protection for child victims of the crime of sexual intercourse in terms of the fulfillment of the right of restitution and find the formulation of the concept of legal protection which is expected to be able to provide legal protection through the fulfillment of the right of restitution in the future. This study uses a normative juridical research method, with a law approach and a case approach. The results of this study are: 1) Legal protection in the form of fulfilling victims' restitution rights, especially in the Gorontalo District Court in practice has not been implemented properly. This is because victims do not know their rights in Article 98 of the Criminal Procedure Code, and the lack of regulation and authority of law enforcement officers in determining the amount of immaterial losses. 2) In order to realize the optimal fulfillment of victims' restitution rights, the provisions regarding restitution in the Witness and Victim Protection Law should be stated in the Criminal Procedure Code so that there is a harmony of arrangements regarding the submission procedure and other provisions regarding restitution. The Draft Criminal Procedure Code must also contain coercive power for the defendant to pay compensation to the victim.